Positive psychology and the I-FLOW model: a new dynamic model of homeostatic wellbeing for mental health nursing. (2nd May 2021) - Macfarlane, Jan
Abstract : This is the tenth article in a series that explores the meaning of positive psychology and the importance of applying the latest related research findings, for the wellbeing of the mental health workforce. It will focus on the innovative I-Flourishing and Languishing Opportunities Wheel (I-FLOW) model, which can be applied to mental health nursing from a different perspective to many other frameworks. It positions realistic optimism and flow at its epicentre, suggesting that these are in a constant dynamic state of homeostatic balance. It recognises that wellbeing can be a combination of managing positive and negative feelings, thoughts and behaviours and that this is central to successful navigation of our life experiences. This article will frame the historical context of the model's development as a multi-dimensional concept through a range of positive psychology theorists and their respective frameworks. Finally, it encourages the reader to consider how the application of I-FLOW could be of benefit to them, through increased self-awareness and feedback. The practical tasks provided in the boxes throughout the article will help the reader identify what flourishing and wellbeing means to them and understand how to further develop its transferability through evidence-based, user-friendly exercises.